2004
DOI: 10.1897/03-351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sedimentary sootlike materials on bioaccumulation and sorption of polychlorinated biphenyls

Abstract: Bioaccumulation of hydrophobic organic chemicals from sediments containing soot or sootlike materials has been hypothesized to be limited by strong sorption of the chemicals to the soot matrixes. To test this hypothesis, we quantified bioaccumulation of 11 polychlorinated biphenyls (PCBs) into the aquatic oligochaete Limnodrilus sp. exposed to spiked sediment with and without the sootlike materials coal and charcoal. In addition, sorption experiments with sediment containing varying amounts of coal or charcoal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
135
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(155 citation statements)
references
References 45 publications
13
135
5
Order By: Relevance
“…In addition, when added to soils, biochar could increase soil nutrients and crop productivity, and improve the soil's physical and chemical properties, such as water retention and nutrient holding capacity (Glaser et al 2009;Laird et al 2010;Paz-Ferreiro et al 2012). Biochar is an excellent sorbent due to its large specific surface area, abundant microporous structure, high hydrophobicity, and aromaticity (Jonker et al 2004). Biochar could effectively remove various pollutants, such as heavy metals, polycyclic aromatic hydrocarbons (PAHs), steroid hormones, pesticides, and antibiotics (James et al 2005;Sarmah et al 2010;Deng et al 2014;Mohan et al 2014;Feng et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when added to soils, biochar could increase soil nutrients and crop productivity, and improve the soil's physical and chemical properties, such as water retention and nutrient holding capacity (Glaser et al 2009;Laird et al 2010;Paz-Ferreiro et al 2012). Biochar is an excellent sorbent due to its large specific surface area, abundant microporous structure, high hydrophobicity, and aromaticity (Jonker et al 2004). Biochar could effectively remove various pollutants, such as heavy metals, polycyclic aromatic hydrocarbons (PAHs), steroid hormones, pesticides, and antibiotics (James et al 2005;Sarmah et al 2010;Deng et al 2014;Mohan et al 2014;Feng et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the size of nonplanar compounds may exceed the average geosorbent pore size and impair electronic interactions between the compound and the geosorbent surface. Therefore, the steric hindrance caused by bulky atoms, like chlorine in highly chlorinated PCBs, reduced sorption of nonplanar compounds to the geosorbent [1,10,11]. However, BC may strongly sorb some nonplanar compounds, for example, the pesticide diuron.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that sorption ability of BC in the field in the presence of organic matter is not as strong as "intrinsic" BC (Cornelissen and Gustafsson, 2004;Jonker et al, 2004). One of the possible mechanisms is the sorption of natural organic matter (NOM) on BC, leading to the sorption site competition and pore blockage.…”
Section: Introductionmentioning
confidence: 99%